Small extracellular vesicles derived from interferon-γ pre-conditioned mesenchymal stromal cells effectively treat liver fibrosis - Takeuchi, Suguru (NPJ Regen Med, 2021)
Mesenchymal stromal cells (MSCs) are used for ameliorating liver fibrosis and aiding liver regeneration after cirrhosis; Here, we analyzed the therapeutic potential of small extracellular vesicles (sEVs) derived from interferon-γ (IFN-γ) pre-conditioned MSCs (γ-sEVs). γ-sEVs effectively induced anti-inflammatory macrophages with high motility and phagocytic abilities in vitro, while not preventing hepatic stellate cell (HSC; the major source of collagen fiber) activation in vitro. The proteome analysis of MSC-derived sEVs revealed anti-inflammatory macrophage inducible proteins (e.g., annexin-A1, lactotransferrin, and aminopeptidase N) upon IFN-γ stimulation. Furthermore, by enabling CX(3)CR1+ macrophage accumulation in the damaged area, γ-sEVs ameliorated inflammation and fibrosis in the cirrhosis mouse model more effectively than sEVs. Single cell RNA-Seq analysis revealed diverse effects, such as induction of anti-inflammatory macrophages and regulatory T cells, in the cirrhotic liver after γ-sEV administration. Overall, IFN-γ pre-conditioning altered sEVs resulted in efficient tissue repair indicating a new therapeutic strategy.